GEOCHRONOLOGY AND GEOCHEMICAL CHARACTERISTICS OF VOLCANIC ROCKS SECTION IN MANZHOULI XINYOUQI, INNER-MONGOLIA - Chen Z.G.; Zhang L.C.; Wan B.; Zhou X.H.; Ying J.F.; Wang F. (My University, 2006)
Mesozoic volcanic rocks section in Manzhouli Xinyouqi, Inner-Mongolia is mainly composed of trachy-andesite, trachyte and rhyolite 40Ar-39Ar dating of lower section trachy-andesites and middle section rhyolites give a plateau age of 162.6 ± 0.7Ma and 162.0 ± 0.8Ma, and zircon U-Pb determination of upper section trachy-andesites yields a concordant age of 149.5 ± 1. 7Ma. This indicates that these volcanic rocks were formed in two gyrations of volcanic explosion in late Jurassic. The major elements of the samples show that geochemical characteristics of rocks in the lower and upper section are similar, which indicate that they formed from the same magma source. Both of them are relatively high in SiO2, A2O3, K2O and total alkaline and low in MgO and Mg#, belonging to the calc-alkaline series with high K contents and demonstrating total REE and LREE enrichment with insignificant Eu anomalies (δEu = 0.72 ~ 0.90) and intense fractionation between LREE and HREE. The primitive mantle-normalized spidergrams are characterized by LILE enrichment and HFSE depletion, especially for a significantly negative Nb-Ta anomaly. Isotopic geochemistry shows that the value of εND (t) range from - 0.5 to 1.3, and (87Sr/86Sr)i from 0.705078 to 0.713891. Rhyolites of middle rocks section are high in SiO2 and low in MgO, FeO and Al2O3, belonging to the calc-alkaline series. Rhyolites display the same REE pattern and εND (t) (-0.7 ~ -0.9)with trachy-andesite and trachyte, while Eu contents appears intense negative Eu anomalies (δEu =0.32), and are characterized by Sr,Ti,Ba and P significant depletion and the high (87Sr/86Sr) i value(0.710044 ~ 0.713891). The geochemical feature of rachy-andesites and trachytes suggest their origination were from a metasomatized mantle wedge or depleted mantle, which had been modified by previous subducted ocean slab. According to the correlation between the rachy-andesites and trachytes, it is inferred that the trachytes were derived from the differentiated crystallization of andesitic magmas. On the other hand, the rhyolites possess a clear "crustal" signature, possibly attributed to the crustal contamination during the magma ascent or anatexis of lower-middle crust in response to the andesitic underplating. Combining their geochemical characteristics with previous studies of this area, the late Jurassic volcanism in Manzhouli Xinyouqi was formed in the post-orogenic stage in which a rapid lithospheric extension must have accurred, resulting in the decompressional. melting of the pre-existent metasomatized lithospheric mantle. It is possibly that these Mesozoic volcanic rocks in Manzhouli Xinyouqi were formed by the collision-postorogenic extension of Mongolia-Okhotsc ocean during late Jurassic.
Keywords: LATE JURASSIC; PETROGEOCHEMISTRY; POST-OROGENIC EXTENSION; XINYOUQI VOLCANIC ROCKS SECTION; Мезозой::Юрская; Mesozoic::Jurassic